Ocular transporters and receptors : their role in drug delivery - Mitra, Ashim K., 1954- (Biohealthcare Publishing series on pharma, biotech and biosciences ;, 2013)
Ocular transporters and receptors contains detailed descriptions of major transporters and receptors expressed in the eye, with special emphasis on their role in drug delivery. The complex anatomy and the existence of multiple barriers in the eye pose a considerable challenge to successful drug delivery to the eye. Hence ocular transporters and receptors are important targets for drug delivery. A significant advancement has been made in the field of ocular transport research and their role in drug delivery. In this book the cutting edge research being carried out in this field is compiled and summarized. The book focuses on key areas, including the anatomy and physiology of the eye, biology of ocular transporters and receptors, techniques in characterization of transporters and receptors, transporters and receptors in the anterior and posterior segment in the eye, the role of ocular transporters and receptors in drug delivery, and transporter-metabolism interplay in the eye. Highly focused on ocular transportersMost up-to-date research compilationDetailed description of role of transporters and receptors in ocular drug discovery and delivery.